Peran Notaris dalam Transformasi Digital Layanan Perizinan Berusaha - Wely Julyan Pratama; Gunawan Edo Wardo; Khalid Muhammad Hadiid; David Samuel Anugrah Pasaribu (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2026)
Digital transformation in public services has become one of the Indonesian government's main agendas to improve bureaucratic effectiveness and facilitate investment. The implementation of the Online Single Submission (OSS) system as an electronic-based business licensing service has transformed the licensing administration pattern from a conventional system to an integrated digital system. In this process, notaries play a crucial role as public officials authorized to issue authentic deeds and guarantee legal certainty for business actors. This study aims to analyze the role of notaries in the digital transformation of business licensing services, examine the challenges faced in implementing digitalization, and examine efforts to strengthen legal regulations in Indonesia. The study uses a normative juridical method with a statutory and conceptual approach. The results show that notaries have a strategic role in the process of establishing a business entity, validating electronic documents, integrating the General Legal Administration (AHU) system with the OSS, and providing legal certainty for digital business transactions. However, digital transformation also presents various challenges, including electronic data security, the use of electronic signatures, limited information technology competency, and synchronization of legal regulations. Therefore, strengthening the digital capacity of notaries, harmonizing regulations, and improving the security of electronic systems are necessary to support the effectiveness of digital-based business licensing services in Indonesia.